Climate change and mental health of Indigenous peoples living in their territory: a concept mapping study - Grande, Antonio Jose; Dias, Ieda M. A. V.; Jardim, Paulo T. C.; Vieira Machado, Alessandra Aparecida; Soratto, Jacks; da Rosa, Maria Inês; Roever, Leonardo; Bisognin Ceretta, Luciane; Zourntos, Xanthi; Harding, Seeromanie (Frontiers in Psychiatry, 2023)
Background The alarming increase in annual deforestation rates has had devastating consequences in climate change, and it is affecting Indigenous people, who depend entirely on the land for survival and has also weakened the rainforest's crucial role in stabilizing the global climate. Recognizing and respecting Indigenous people's needs and social, economic, and historical conditions influence health and healthcare. This study aimed to conduct online concept mapping workshops with university students to identify perceived important and feasible actions for improving the mental health of Indigenous people living in their territory in association with climate change. Methods Concept mapping, a participatory mixed methodology, was conducted virtually with 20 Indigenous students at two universities in Brazil. A focus prompt was developed from consultations with Indigenous stakeholders and read—“To improve the mental health of Indigenous peoples in their territory during climate change crises, it is necessary to….” Results University students organized 42 unique statements in 6 clusters that cover a wide range of topics: family support, 0.68 (SD 0.19); respect and understanding, 0.37 (SD 0.08); improvement actions, 0.52 (SD 0.07); public policies in favor of Indigenous people's mental health, 0.24 (0.09); health actions, 0.15 (SD 0.08); Indigenous training in health and its importance in improving mental health 0.32 (SD 0.07). Conclusion These clusters range from community initiatives, public policies, health actions, and strengthening professional services in Indigenous communities. These all provide numerous concrete ideas for developing interventions designed to address mental health challenges associated with climate change.